Outside Options and Worker Motivation - Alexander Ahammer; Matthias Fahn; Flora Stiftinger (Institute of Labor Economics (IZA), 2023)
We study the relationship between outside options and workers' motivation to exert effort. We evaluate changes in outside options arising from age and experience cutoffs in the Austrian unemployment insurance (UI) system, and use absenteeism as a proxy for worker effort. Results indicate that a one-percent increase in the potential UI benefit duration increases absenteeism at the intensive margin by 0.28 percent. These results are consistent with a relational contracting model where effort is constrained by the future value of an employment relationship. This model further predicts that effort reductions are more pronounced if benefits assume a larger role in a worker's outside option and if the perceived relationship value is small. Indeed, we find that our effects are stronger for workers with higher potential cost of unemployment, for older workers, in declining rather than in growing firms, in low-wage firms, and for women as well as workers with children.
Keywords: D21; D22; J22; J53; M52; 330; outside options; effort incentives; relational contracts